2008
DOI: 10.1021/nl802058q
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Sub-Diffraction Limit Encounters in Nanoparticle Tracking Using Live Cell Plasmon Coupling Microscopy

Abstract: We use plasmon coupling between individual gold nanoparticle labels to monitor sub-diffraction limit distances in live cell nanoparticle tracking experiments. While the resolving power of our optical microscope is limited to ~500 nm, we improve this by more than an order of magnitude by detecting plasmon coupling between individual gold nanoparticle labels using a ratiometric detection scheme. We apply this plasmon coupling microscopy to resolve the interparticle separations during individual encounters of gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
126
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 53 publications
0
126
0
Order By: Relevance
“…Furthermore, the inter-particle separation can be seen clearly among the Au nanoparticles produced at 532 nm, whereas almost all of the Au nanoparticles produced at 1064 nm are stuck together, forming chains. Rong et al [40,41] showed that if the inter-particle separations (D) are larger than the particle diameter (D) (D [ D), ''the near-field interaction between the particles is small and the resonance wavelength k res is that of an individual particle'', but if the inter-particle separations are smaller than the particle diameter (D [ D), ''the plasmons in the individual particles couple and the resonance wavelength k res red shifts with decreasing separation''. They observed the red-shift phenomena while increasing the intensity ratio (R = I 580 nm /I 530 nm ).…”
Section: Effects Of Wavelengths On the Size Of The Nanoparticlesmentioning
confidence: 99%
“…Furthermore, the inter-particle separation can be seen clearly among the Au nanoparticles produced at 532 nm, whereas almost all of the Au nanoparticles produced at 1064 nm are stuck together, forming chains. Rong et al [40,41] showed that if the inter-particle separations (D) are larger than the particle diameter (D) (D [ D), ''the near-field interaction between the particles is small and the resonance wavelength k res is that of an individual particle'', but if the inter-particle separations are smaller than the particle diameter (D [ D), ''the plasmons in the individual particles couple and the resonance wavelength k res red shifts with decreasing separation''. They observed the red-shift phenomena while increasing the intensity ratio (R = I 580 nm /I 530 nm ).…”
Section: Effects Of Wavelengths On the Size Of The Nanoparticlesmentioning
confidence: 99%
“…Instruments based on hyperspectral darkfield have enabled quantitative molecular imaging [22] and spectral multiplexing [7], using functionalized nanoparticles where an antibody conjugate provides molecular specificity [4,23]. These instruments are even capable of detecting plamonic shifts due to coupling which can then be used to provide additional spatial information [24][25][26]. However, a key limitation of this approach is that the detailed structure of the cells is not imaged directly using the nanoparticle tagging and instead must be inferred.…”
Section: Darkfield Microspectroscopymentioning
confidence: 99%
“…Discrete nanoparticles, however, can be suspended in solution, which may be beneficial in some applications, where sensing within living cells is one recent example. 28 On the other hand, the continuity of metal films perforated with nanoholes provides a unique opportunity for combining nanoplasmonic sensing with other transducer formats that rely on electrical readout. These aspects, which are of outmost importance depending on the systems under investigation, are addressed with suitable examples from us and others, with focus on the use of nanoplasmonic sensors to analyze biomolecular structural changes and means to quantify the response from nanoplasmonic sensors in terms of bound molecular mass.…”
Section: Introductionmentioning
confidence: 99%